Legal Protection in The Settlement of Industrial Relations Disputes in Indonesia - Tamba, Tumanda; Juita, Subaidah Ratna; Astanti, Dhian Indah (Jurnal Justiciabelen, 2023)
Article 2 of Law Number 2 Year 2004 states that there are four types of industrial relations disputes consisting of Rights Disputes, Interest Disputes, Termination of Employment Disputes and Disputes Between Workers / Labor Unions in One Company. This research uses normative juridical methods, the results of the study explain the form of legal protection in the settlement of industrial relations disputes in Indonesia outside the court can be done through: Bipartite, Mediation, Conciliation, Arbitration The four types of settlement If the negotiations reach an agreement, a collective agreement is made binding and becomes law for the parties. The collective agreement must be registered with the Industrial Relations Court at the District Court in the area where the parties entered into the collective agreement if it is not implemented by one of the parties, the injured party can apply for execution to the Industrial Relations Court. In addition to the above 4 explanations, the settlement of industrial relations disputes can be through the industrial relations court which is in the general judicial environment, which is limited in its process and stages by not opening the opportunity to file an appeal to the superior court.The decision of the industrial relations court at the district court which concerns rights disputes and employment termination disputes can be directly appealed to the Supreme Court.